Prayer in the Cave of the Heart : The Universal Call to Contemplation - Consiglio, Cyprian (Book collections on Project MUSE., 2010)
Prayer is an art that cannot just be taught. It must be experienced, lived, and practiced. In Prayer in the Cave of the Heart, Cyprian Consiglio draws on his experience as a Camaldolese monk to give readers an accessible reflection on prayer that is based on Bede Griffith's universal call to contemplation. In this text, the contemplative traditions of East and West intersect to invite readers into prayer that makes them 'present to the Spirit who is already present to us.'